Financial Performance Evaluation of PT Mitra Keluarga Karyasehat Tbk: Financial Ratio Analysis 2022-2023 - Subagyo, Imam; Ramadhan, Yanuar; Sandrawati, Agnes; Kumala, Ratna Dewi; Andika, Dede (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze the financial performance of PT Mitra Keluarga Karyasehat Tbk using various financial ratio analysis methods. The analysis was carried out on the company's financial statements for the periods 2022 and 2023. The methods used include analysis of liquidity, activity, leverage, and profitability ratios. The results of the study show that PT Mitra Keluarga Karyasehat Tbk experienced an increase in liquidity and a reduction in leverage, but faced a decline in operational efficiency and profitability. The Current Ratio increased from 3.82 in 2022 to 4.97 in 2023, and the Quick Ratio increased from 3.73 to 4.82. However, Receivable Turnover and Inventory Turnover decreased, indicating a decrease in the efficiency of current asset management. The leverage ratio shows a decrease in dependence on debt, but the Interest Coverage Ratio decreased from 104.16 to 77.88, indicating a decrease in the ability to cover interest expenses. The profitability ratio decreased, indicating the need for improvements in cost management and revenue-increasing strategies. Overall, the company needs to focus on improving operational efficiency and cost management to improve financial performance in the future.